The role of perioperative sodium bicarbonate infusion affecting renal function after cardiothoracic surgery - Turner, Katja R.; Fisher, Edward C.; Hade, Erinn M.; Houle, Timothy T.; Rocco, Michael V. (Frontiers in Pharmacology, 2014)
Cardiac surgery associated acute kidney injury (CSA-AKI) is associated with poor outcomes including increased mortality, length of hospital stay (LOS) and cost. The incidence of acute kidney injury (AKI) is reported to be between 3 and 30% depending on the definition of AKI. We designed a multicenter randomized controlled trial to test our hypothesis that a perioperative infusion of sodium bicarbonate (SB) during cardiac surgery will attenuate the post-operative rise in creatinine indicating renal injury when compared to a perioperative infusion with normal saline. An interim analysis was performed after data was available on the first 120 participants. A similar number of patients in the two treatment groups developed AKI, defined as an increase in serum creatinine the first 48 h after surgery of 0.3 mg/dl or more. Specifically 14 patients (24%) who received sodium chloride (SC) and 17 patients (27%) who received SB were observed to develop AKI post-surgery, resulting in a relative risk of AKI of 1.1 (95% CI: 0.6–2.1, chi-square p-value = 0.68) for patients receiving SB compared to those who received SC. The data safety monitoring board for the trial recommended closing the study early as there was only a 12% probability that the null hypothesis would be rejected. We therefore concluded that a perioperative infusion of SB failed to attenuate the risk of CSA-AKI.